Problems of Supervisors in the Implementation of Guidance and Counseling in Schools: Solutions to Problems as Operations and Follow-up - Deliati; Neviyarni S; Firman (Manajia: Journal of Education and Management, 2025)
Supervision is essentially building legal compliance, namely compliance with binding laws and regulations and institutional provisions. The duties and responsibilities of supervisors in the field of guidance and counseling refer to (Depdiknas, 2009 which refers to PP No. 74 of 2008). The purpose of this study is to provide information on improving the ability of BK teachers in utilizing the learning environment and improving the ability of BK teachers in compiling and implementing BK programs in schools is one of the objectives of supervision. The elements of supervision are educational supervisors, academic and managerial supervision, professional development supervisors, and supporting supervisors. The problem that we often encounter is that there are still many school/madrasah supervisors who do not know and understand the roles they must carry out and the functions they carry out. For this reason, efforts or solutions that must be taken immediately are that the government should conduct an objective review of the performance of school supervisors, then supervisors should be encouraged to participate in supervision training carried out by the government or related agencies in order to be able to find out about information developments and improve the competence of a supervisor. The methods used are literature studies and survey methods. Data collection techniques are sourced from various relevant literature and have been discussed in previous articles and are faced with conditions in the field regarding the dynamics of operational supervision and performance of BK teachers in schools.